1994
DOI: 10.1136/gut.35.10.1464
|View full text |Cite
|
Sign up to set email alerts
|

Common bile duct stones are mainly brown and associated with duodenal diverticula.

Abstract: This study investigated the composition of common duct gall stones from 61 patients, aged

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Due to the difficulty of obtaining both bile and stones at the same time at ERC, the composition of stones was not investigated in this study, but we have previously found that about 70% of common bile duct stones in our Scandinavian patient population are brown, even with coexisting cholecystolithiasis [8], Our patient population differs considerably from series obtained at cholecystecto my or even laparoscopic surgery, and may not be directly comparable with such series. Our patients are those referred for ERC in a tertiary care endoscopy unit where the mean age of the general patients population is 75 years, 56% arc women, and the primary problem is more frequently those of common duct stones rather than gall bladder stones.…”
Section: Lps |)-Glucuronidase and Choledocholithiasismentioning
confidence: 58%
See 2 more Smart Citations
“…Due to the difficulty of obtaining both bile and stones at the same time at ERC, the composition of stones was not investigated in this study, but we have previously found that about 70% of common bile duct stones in our Scandinavian patient population are brown, even with coexisting cholecystolithiasis [8], Our patient population differs considerably from series obtained at cholecystecto my or even laparoscopic surgery, and may not be directly comparable with such series. Our patients are those referred for ERC in a tertiary care endoscopy unit where the mean age of the general patients population is 75 years, 56% arc women, and the primary problem is more frequently those of common duct stones rather than gall bladder stones.…”
Section: Lps |)-Glucuronidase and Choledocholithiasismentioning
confidence: 58%
“…Both the old age and lack of a clear female predominance makes it likely that most stones are brown pigment stones also in this material. Black stones were rare [8], similar to what is found in Americans of Scandinavian descent [3]. Even migrating stones from the gallbladder, once entering the common bile duct, will be exposed to the lithogenicity of common duct bile which usually favors pigmentary salt deposition [27], Migrating stones may thus serve as foreign material in the common duct.…”
Section: Lps |)-Glucuronidase and Choledocholithiasismentioning
confidence: 79%
See 1 more Smart Citation
“…), of the stones were compared with those of 1 mg pure cholesterol (Sigma, St. Louis, Mo., USA) or bilirubinate [5]. For analysis of cholesterol content a wavelength of 1,055 cm –1 and for bilirubinate wavelengths of 1,662 and 1,622 cm –1 were chosen for quantitation [4, 6]as previously reported [1]. …”
Section: Methodsmentioning
confidence: 99%
“…Common bile duct stones are mainly brown pigment stones, containing only small amounts of cholesterol [1]. Factors leading to precipitation and aggregation of calcium bilirubinate, proteins and fatty acids that make up the main components of brown stones are uncertain.…”
Section: Introductionmentioning
confidence: 99%